Impoverishment Punishment as a Progressive Approach in Handling Corruption: Legal Studies and Practices in Indonesia - Yasmirah Mandasari Saragih; Rahul Ardian Fikri; Nabilah Syaharani (International Forum of Researchers and Lecturers, 2024)
Corruption is one of the criminal acts that has a destructive impact on development and public trust. In an effort to strengthen the eradication of corruption, impoverishment punishment is proposed as a progressive approach that aims to provide a deterrent effect and restore state losses. This study aims to analyze the effectiveness of the application of impoverishment punishment in handling corruption in Indonesia. The method used is a juridical-sociological approach, by examining applicable regulations and the impact of their application in practice.The results of the study show that impoverishment punishment has great potential in reducing corruption rates, especially with the confiscation of assets from crime which can reduce the motivation of perpetrators to commit corruption. However, the implementation of this punishment faces various challenges, including the lack of regulatory synchronization, technological limitations in asset tracking, and political resistance. This study recommends strengthening regulations, increasing the capacity of financial forensic technology, and public education to support the effective implementation of impoverishment punishment. With the right strategy, impoverishment punishment can be one of the key instruments in building a stronger and more equitable corruption eradication system.